2005
DOI: 10.1039/b416476h
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurements of the flow velocities in a microchannel by wide/evanescent field illuminations with particle/single molecules

Abstract: A laser-induced fluorescence imaging method was developed to simultaneously measure flow velocities in the middle and near wall of a channel with particles or single molecules, by selectively switching from the wide field excitation mode to the evanescent wave excitation mode. Fluorescent microbeads with a diameter of 175 nm were used to calibrate the system, and the collisions of microbeads with channel walls were directly observed. The 175 nm microbeads velocities in the main flow and at 275 nm from the bott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Additional functionalities can be built into the OFM systems. For example, the capability to perform fluorescence imaging [15,27] or Raman imaging [28] can be added In fact, the on-chip nature of the OFM easily enables multispectral analysis. A series of OFM device, each selective for a given wavelength band, can be built along a single microfluidic channel.…”
Section: Discussionmentioning
confidence: 99%
“…Additional functionalities can be built into the OFM systems. For example, the capability to perform fluorescence imaging [15,27] or Raman imaging [28] can be added In fact, the on-chip nature of the OFM easily enables multispectral analysis. A series of OFM device, each selective for a given wavelength band, can be built along a single microfluidic channel.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing this system, we developed a novel method for simultaneous measurement of flow velocities in the middle and near wall of a microchannel with particles or single molecules. 34 In addition, we found that the numbers of molecules probed in the evanescent field decreased with an increase of molecular weight because of steric hindrance. 35 This interesting phenomenon might be helpful for studying undefined molecular interactions at extremely low concentrations without need of separations.…”
Section: Single Molecule Detectionmentioning
confidence: 96%
“…Evanescent wave-based particle velocimetry methods have been used by various researchers to study Poiseuille and electroosmotic flows and hindered Brownian diffusion [5][6][7]. A number of groups have also used zinc sulfide-overcoated cadmium selenide quantum dots, which emit in the visible portion of the spectrum [8], and fluorescently labeled DNA molecules [9], as flow tracers for evanescent-wave velocimetry.…”
Section: Introductionmentioning
confidence: 99%